2015
DOI: 10.1093/cid/civ678
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Engagement in HIV Care: An Important Predictor of Long-term Retention in Care and Viral Suppression

Abstract: The prevalence of postpartum HIV-infected women retained in care and maintaining viral suppression is low. Interventions seeking to engage women in care shortly after delivery have the potential to improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 33 publications
9
62
1
4
Order By: Relevance
“…A recent study concluded that HIV-infected women on suppressive combination antiretroviral therapy, the risk of viral rebound is increased during postpartum, especially in the first 3 months, which may be related to reducing adherence (Huntington 2015). Also, postpartum viral rebound was linked with fewer prenatal visits and later gestational week of starting prenatal care (Cavallo 2010;Adams 2015). Indicating then the need for effective adherence interventions as well as in prenatal and postpartum period.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…A recent study concluded that HIV-infected women on suppressive combination antiretroviral therapy, the risk of viral rebound is increased during postpartum, especially in the first 3 months, which may be related to reducing adherence (Huntington 2015). Also, postpartum viral rebound was linked with fewer prenatal visits and later gestational week of starting prenatal care (Cavallo 2010;Adams 2015). Indicating then the need for effective adherence interventions as well as in prenatal and postpartum period.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Postpartum engagement in HIV care was defined as having ≥1 CD4 or VL in the first 90 days post-delivery (Adams et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Depression can be a strong predictor of non-adherence to antiretroviral therapy (ART) (Ammassari, Antinori, Aloisi, Trotta, & Murri, 2004; Springer, Dushaj, & Azar, 2012) and may contribute to poor maternal outcomes at delivery and postpartum (Alder, Fink, Bitzer, Hösli, & Holzgreve, 2007; Goedhart et al, 2010). Previous studies have shown that WLWH have poor viral suppression at delivery (Momplaisir et al, 2015) and poor retention in HIV care postpartum (Adams, Brady, Michael, Yehia, & Momplaisir, 2015; Momplaisir, Storm, Nkwihoreze, Jayeola, & Jemmott, 2018). The impact of depression on HIV care outcomes during pregnancy and postpartum has not been well described.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, breastfeeding is not recommended given access to safe formula [12]. After delivery, establishment and maintenance of HIV care is critical to maternal health, prevention of HIV transmission to partners and prevention of perinatal transmission during subsequent pregnancies [13]. Referral to an infectious disease specialist is strongly recommended.…”
Section: Hiv Infection During Pregnancymentioning
confidence: 99%
“…A history of a prior pregnancy with HIV infection is associated with better compliance with retention in care. Women who were engaged in HIV care early after delivery, particularly within the first 90 days postpartum, were more likely to remain in care and virally suppressed at 1 and 2 years, compared with those who were not engaged early after delivery [13], suggesting that interventions focusing on early engagement in care during the immediate postpartum period may help with long-term retention and viral suppression. Only a third of women remained virally suppressed at 1 and 2 years postpartum, demonstrating a significant shortfall in the HIV Care Continuum among reproductive age women in the USA [7,17].…”
Section: Postpartum Strategies To Achieve Successful Engagement Into mentioning
confidence: 99%